Doing safe by doing good: ESG investing and corporate social responsibility in the U.S. and Europe - Christina E. Bannier; Yannik Bofinger; Björn Rock (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
This paper examines the profitability of investing according to environmental, social and governance (ESG) criteria in the U.S. and Europe. Based on data from 2003 to 2017, we show that a portfolio long in stocks with the highest ESG scores and short in those with the lowest scores yields a significantly negative abnormal return. Interestingly, this is caused by the strong positive return of firms with the lowest ESG activity. As we find that increasing ESG scores reduce firm risk (particularly downside risk), this hints at an insurance-like character of corporate social responsibility: Firms with low ESG activity need to offer a corresponding risk premium. The perception of ESG as an insurance can be shown to be stronger in more volatile capital markets for U.S. firms, but not for European firms. Socially responsible investment may therefore be of varying attractiveness in different market phases.
urn:nbn:de:hebis:30:3-480587
Keywords: G11; G32; G34; O16; Q56; 330; ESG; corporate social responsibility; sustainability; downside risk; insurance; Fama-French model; dynamic panel GMM estimation